(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ملخص : جمال القرآن جمال متفرد، لا يماثله جمال أو يقترب منه، والفاصلة القرآنية لوحة جمالية من جمالياته وركيزة بيانية في نظمه، وركن بارز في تركيبه، تضفي عليه جمالاً وإعجازاً، والمتذوق للغة الخطاب القرآني، يدرك مكانة الفاصلة القرآنية وموقعها وهدفها من حيث دلالة المعنى ودلالة الإيقاع معًا، فهي تخلب اللب، وتأخذ بالإحساس، وتمتلك النفس، شديدة الارتباط بالمعنى، واختلاف الفواصل يفضي إلى اختلاف المعاني، وتكرارها بلفظ واحد فيه تأكيد ومبالغة، فهي قيمةٌ جمالية صوتيةٌ، لها وظيفةٌ مهمةٌ بما تحمله من إيحاءات ومعان، يراعى فيها اللفظ والجرس والدلالة. الكلمات الدالة: الخطاب القرآني - الفاصلة القرآنية – جماليات Abstract: The beauty of Quran is unique. No beauty is similar or close to it The koranic comma is one of its painting aesthetics and a graphic anchor of its composition. It gives Quran beauty and miracle. The connoisseur of the language of the Quran discourse understands the status ,location and aim of the koranic comma in terms meaning and rythm together. It exudes the pulp ,takes the feeling and possesses the soul .It is closely related to the meaning and different different separations add different meanings .Its repetition in one word has affirmation and exageration. It is an aesthetic and acoustic value. It has an important function including references and meanings,taking into account the prononciation,intonation and significance. Keywords: Aesthetisc - Quranic discourse - Quranic comma